Impact of modulation of telomerase and cancer stem‐cell marker OCT4 axis in cervical cancer pathogenesis with underlying HPV16 infection. Issue 4 (6th November 2019) - Tiwari, Diptika; Ray Das, Chandana; Sultana, Rizwana; Kakoti, Shantipriya; Aasif Khan, Mohammad; Dongre, Anita; Husain, Syed Akhtar; Bose, Purabi Deka; Bose, Sujoy
Abstract: Lacunae exist in the molecular event(s) specificity associated with cervical cancer (CaCx) pathogenesis. The present study aimed to evaluate the significance of telomerase‐cervical cancer stem cells (CSCs) modulation in CaCx pathogenesis with underlying HPV16 infection. The study included HPV16 positive cases only ( N  = 65) of the total enrolled cases from Northeast India. The analysis of viral load and the differential messenger RNA expression of E6, E7, hTERT, hTR, and cancer stem‐cell markers was studied by real‐time polymerase chain reaction. Further the protein and colocalization study for E6, hTERT, and oct4 was performed by immunofluorescence. The real‐time polymerase chain reaction based analysis showed an upregulation of HPV16 viral oncoprotein E6 and E7, and telomerase component hTERT and hTR expression and their correlation in CaCx susceptibility and severity. The hTERT expression correlated with viral load; while the E6 and telomerase protein expression colocalized in the nucleus. The CSCs marker octamer‐binding transcription factor 4 (OCT4) was significantly upregulated in CaCx cases, was associated with CaCx susceptibility and severity, and colocalized with E6 expression in the nucleus as revealed from the immunofluorescence studies. To conclude, the telomerase‐OCT4 axis modulation holds key in HPV16 CaCx pathogenesis mediated by HPV16 E6 viral oncoprotein expression, and underlines its potential for therapeutic targeting.